STUDY OF POTENTIAL INSTALLATION OF OCEAN THERMAL ENERGY CONVERSION (OTEC) IN THE NORTH WATERS OF LEMBATA, NTT - Gisela Malya Asoka; Denny Nugroho Sugianto; Yani Permanawati (BULLETIN OF THE MARINE GEOLOGY, 2023)
Ocean thermal energy conversion is an attempt to convert potential energy in the variances heat content of seawater into other energy by utilizing the temperature change between the sea surface and deep sea at least 20°C. The Lembata waters is near to the equator, sea surface temperature tends to be warm and stable. This research was conducted to estimate the potential energy generated from a closed cycle OTEC system in North Lembata Waters. This study used temperature data from Global Ocean Physics Reanalysis from Copernicus Marine Environment Monitoring Service (CMEMS) for 9 years (2012-2020) in 6 stations. Validation was performed using the primary CTD Lembata OTEC Team of the Marine Geological Institute (MGI). Temperature data validation results on the MSE (Mean Square Error), RMSE (Root Mean Square Error), and MAPE (Mean Absolute Percentage Error) methods are considered to represent field temperature conditions. The variability value shows the station point in the North Lembata Waters has a temperature with slight differences. The vertical temperature change (ΔT) shows between 20.98°C to 23.44°C. Potential electric power resulting from the OTEC system using the technical estimation formula. The average net power generated from those temperature gradients ranges from 5.65 MW-7.56 MW, respectively. The Lembata waters have temperature conditions suitable for OTEC installations. Station C-4 has a power potential of 6.84 MW with a depth of 763 m and the distance of 1.86 km from the coastline. Station C-4 in the Omesuri sub-district is the best point for OTEC installation in North Lembata Waters.